2019
DOI: 10.1039/c9ra06572e
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric ceramics/TiO2/single-crystalline silicon nanomembrane heterostructure for high performance flexible thin-film transistors on plastic substrates

Abstract: Dielectric ceramics/TiO2/single-crystalline silicon nanomembrane heterostructure for high performance flexible thin-film transistors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…However, the dielectric layer maintained good stability at high frequency. The dielectric constant ε r of the PS layer was calculated to be ∼2.6 (approximately consistent with ref and ) according to the equation where ε 0 is the vacuum permittivity, C i is the quasi-static unit-area capacitance, and d is the thickness of the PS dielectric layer. Furthermore, the dielectric loss also remained at ∼0.04 within the range 10–10 6 Hz.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…However, the dielectric layer maintained good stability at high frequency. The dielectric constant ε r of the PS layer was calculated to be ∼2.6 (approximately consistent with ref and ) according to the equation where ε 0 is the vacuum permittivity, C i is the quasi-static unit-area capacitance, and d is the thickness of the PS dielectric layer. Furthermore, the dielectric loss also remained at ∼0.04 within the range 10–10 6 Hz.…”
Section: Resultssupporting
confidence: 69%
“…The maximum transconductance reached ∼6.5 μS at an applied gate voltage of ∼1.35 V. During the annealing process, the effective distance between the doped regions ( L ) may become slightly smaller than 4 μm (∼3.8 μm) because of ion diffusion. , Therefore, the calculated mobility taking into account the diffusion effect should be appropriate according to the equation where C ox is the quasi-static unit-area capacitance of the gate dielectric. The effective channel electron mobility was calculated to be ∼120 cm 2 V –1 S –1 , comparable to those of SiNM TFTs based on inorganic dielectrics ,, and much higher than those of TFTs based on amorphous, polycrystalline, and organic semiconductors. , An ∼250 mV/dec subthreshold swing (SS) was also calculated by the equation which indicated that the TFT can operate at high speed in the subthreshold region. The interfacial trap density ( D it ) can be obtained through the equation where k is the Boltzmann constant, T is the absolute temperature, q is the unit electron charge, and C ox is the quasi-static unit-area capacitance of the gate dielectric.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations